The Determinants of Participation in Vocational Training in Albania - Alikaj, Lorena; Guga, Klaudja (European Scientific Journal, ESJ, 2017)
The Albanian labour market has changed drastically during the last two decades as a result of technological developments, labour force mobility, structural unemployment etc. New skills are required by firms and many types of skills turned to be obsolete and no longer in demand. The article tries to analyze the situation in the Albanian labour market, in order to identify the actual trend and to explain theoretical reasons and determinants that cause it. Using Labour Force Survey data it’s aimed an empirical model to evaluate the determinants of employees’ participation in vocational training in Albania. Based on the empirical literature such determinants can be person related, job related, and employer related. The findings from this paper will be compared with findings from the literature in order to see differences and similaritiesare.